PENGARUH SUKU BUNGA DAN KURS TERHADAP HARGA SAHAM PERUSAHAAN REAL ESTATE DAN PROPERTY (KAJIAN EMPIRIS PADA BURSA EFEK INDONESIA ) PERIODE BULANAN 2013-2014 - Savira, Rahmadya; Rimbano, Dheo (MOTIVASI, 2016)
Purpose - This study aims to determine the effect of the stock price with interest rate and the exchange rate as an independent variable.Design/methodology - The analysis period was 24 months starting from 2013 to 2014. The data analysis method used is descriptive analysis.Findings – The results showed that variable interest rates and exchange rates have a significant effect on stock prices with a coefficient of determination of R2 15.3%. The parsial test showed that interest rates variable have a significantly effect on the price of shares in the Indonesian Stock Exchange (BEI) with the obtained results of data processing test obtained t arithmetic ≤ t table (0.003 ≤0,05) H0 is rejected. Then rate variable also significantly influence stock prices by the results obtained test data processing obtained t arithmetic ≤ t table (0.007 ≤0,05) H0 is rejected. This means that interest rates and exchange jointly affect the price of shares in real estate companies and property in the Indonesia Stock Exchange.